1987
DOI: 10.2527/jas1987.6551327x
|View full text |Cite
|
Sign up to set email alerts
|

Induced Non-Enzymatic Browning of Soybean Meal. III. Digestibility and Efficiency of Protein Utilization by Ruminants of Soybean Meal Treated with Xylose or Glucose

Abstract: Trials were conducted to evaluate effects of non-enzymatic browning of soybean meal (SBM) on efficiency of protein utilization and N digestibility. In trial 1, 48 Suffolk-Finnsheep lambs (22 kg) were fed 80 d to evaluate efficiency of protein utilization for growth when supplemental protein was fed as urea (U), commercial SBM (CS), or commercial SBM (pH 8.5, 83% dry matter) containing xylose (3 mol/mol SBM-lysine) and heated 30 min (XTS-30) or 55 min (XTS-55). Diets containing graded levels of N from CS, XTS-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…(1992) showed that the distillers' products were the only materials whose ADIN exhibited high apparent digestibilities among the feeds tested. The amino‐carbonyl reaction occurs between the free amino groups of proteins and the carbonyl residues of reducing sugars, and the intensity of this reaction was especially higher between lysine (Ashoor & Zent 1984; Craig & Broderick 1984) and xylose (Lewis & Lea 1950; Cleale et al . 1987).…”
Section: Discussionmentioning
confidence: 99%
“…(1992) showed that the distillers' products were the only materials whose ADIN exhibited high apparent digestibilities among the feeds tested. The amino‐carbonyl reaction occurs between the free amino groups of proteins and the carbonyl residues of reducing sugars, and the intensity of this reaction was especially higher between lysine (Ashoor & Zent 1984; Craig & Broderick 1984) and xylose (Lewis & Lea 1950; Cleale et al . 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, acid detergent insoluble N (ADIN) has been used as a measure of heat damage in non‐forage plant protein sources,5–7 but some evidence suggests that this relationship is very poor 8–10. Nakamura et al 11 observed that, although ADIN increased in heat‐damaged non‐forage protein sources, this increase was not a one‐to‐one relationship with indigestible protein.…”
Section: Introductionmentioning
confidence: 99%
“…Nakamura et al 11 observed that, although ADIN increased in heat‐damaged non‐forage protein sources, this increase was not a one‐to‐one relationship with indigestible protein. Indeed, evidence suggests that ADIN is partially digestible8, 10, 12 and overestimates heat damage 9, 10, 13. However, these studies evaluated heat‐damaged protein through N digestibilities that do not necessarily reveal the metabolism of ingested N. The results obtained by Nakamura et al 14 with growing ruminants suggest that some of the N in heat‐damaged protein was absorbed post‐ruminally but was not used for growth.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementing ruminant diets with high quality RUP sources may increase the flow of nitrogen and AAs to the small intestine (Zinn et al, 1981), which may consequently improve growth performance in animals (Goedeken et al, 1990). Treating SBM with xylose may reduce degradation of SBM protein (Cleale et al, 1986;Ipharraguerre et al, 2005) and thereby may increase the proportion of RUP and intestinal AA supply. It has been shown that post-ruminal supply of AA increased nitrogen retention and thus caused increased rates of gain (Richardson and Hatfield, 1978).…”
Section: Discussionmentioning
confidence: 97%
“…However, during heat treatment of protein-reach feeds, temperature and duration of heating must be under careful control in order to optimise the content of digestible RUP (Schwab, 1995). Treatment of SBM with xylose which was first introduced by Cleale et al (1986) reduced degradation of SBM protein in rumen and consequently increased the proportion of RUP in SBM. Jahani-Moghadam et al (2009) demonstrated that replacing SBM with XSBM had positive effects on efficiency of lactating dairy cows.…”
Section: Introductionmentioning
confidence: 99%